Analysis of Clavicle in Nepalese Population - Haque, M K; Mansur, D I; Krishnamurthy, A; Karki, R; Sharma, K; Shakya, R (Kathmandu University Medical Journal, 2012)
Background Determining the sex of deceased is easy when a complete skeleton is available for examination. On the whole, the bones are heavier, larger and markings of muscular attachments are more pronounced in the male than in the female. Objective The purpose of this study was attempted to evolve an easily applied formula to enable the assessment of sex in an unknown clavicles and to know about comparative differences between the right and left clavicles, from certain metrical parameters. Methods The study was an observational, cross-sectional and descriptive in nature. The present study was conducted on 257 adult clavicles out of which, 135 were of the right side and 122 of left side. The maximum length of the clavicle (in mm) was taken. Results The length of the right clavicles varies from 108 mm to 178 mm with an average of 143.21 mm ±11.13 mm S.D. The length of the left clavicles varies from 111mm to 181 mm with an average 145.53 mm ±11.04 mm S.D. It has been observed that the left clavicle was longer than the right clavicle by 2.32 mm. There was no such single character which can determine the sex of all clavicles. Depending on the length alone, the sex can be decided in 13.33% male and 4.44% female right clavicles and 16.39% male and 9.83% female bones if the left clavicle is considered. Conclusion The left clavicle was longer than the right clavicle. The determination of sex from the clavicle has a great medico legal significance to the toxicologists. It also helps the anthropologists in their study of evolution of mankind and migration of races. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6304 Kathmandu Univ Med J 2011;9(3):193-7